Assessment of Some Widely Consumed Sachet and Bottled Water Brands; Implications for Radiation Risks in Ondo and Ekiti State, South Western Nigeria - Adeojo, Taiwo Temitope; Adebisi, Warith Adewale; Adeojo, Ifedayo Olukemi; Adewumi, Olumuyiwa Femi; Babalola, Khadijat Kuburat; Azeez, Surajudeen Otolowo (Iraqi Journal of Science, 2025)
In recent years, drinking water in bottles or sachets has become increasingly accepted in major towns and cities in Ekiti and Ondo states, southwestern Nigeria. Selected sachet and bottled water based on a wide range of consumer samples were collected from various manufacturers and distributors in both states. Activity concentrations of natural radioactivity, including 40K, 226Ra and 232Th, were measured using a gamma ray spectrometer with a high-purity germanium detector (HPGe). The activity concentration of40K, 226Ra and 232Th ranged from 0.46 0.02 to 4.74 0.44 Bq L-1, 0.14 0.01 to 1.62 0.30 Bq L-1, and 0.16 0.11 to 1.42 0.21 Bq L-1, respectively in sachet water. Activity concentration values in bottled water for 40K, 226Ra and 232Th ranged from 0.72 0.10 to 2.32 0.14 Bq L-1, 0.15 0.01 to 0.82 0.03 Bq L-1, and 0.19 0.03 to 1.42 0.10 Bq L-1, respectively. Determined ingested annual effective dose on the scale of International Commission on Radiological Protection (ICRP) for the age groups of 0-1y, 1-2y, 2-7y, 7-12y, 12 -17y and > 17y from consumption of the water samples are 0.831 mSvy-1, 0.258 mSvy-1, 0.204 mSvy-1, 0.245 mSvy-1, 0.620 mSvy-1, 0.261 mSvy-1 respectively for sachet water, it is 0.613 mSvy-1, 0.118 mSvy-1, 0.156 mSvy-1, 0.175 mSvy-1, 0.428 mSvy-1, 0.203 mSvy-1, respectively for bottled water. The mean contributions of 40K, 226Ra and 232Th activities of both water type samples in the study area from an annual volume consumption is higher than the recommended tolerable limit of 0.1 mSvy-1 or lower as reported by WHO. It is therefore strongly recommended that nursing mothers should guard the lactating populace from the consumption of the surveyed samples to minimize the stochastic risk of radiation hazards in infants.